The Oxford handbook of social movements - Della Porta, Donatella 1956-; Diani, Mario 1957- (Oxford Oxford University Press, 2017)
The Oxford handbook of social movements' is an innovative volume that presents a comprehensive exploration of social movement studies, mapping the field and expanding it to examine the recent developments in cognate areas of studies, within and beyond sociology and political science. This volume brings together the most distinguished social and political scientists working in this field, each writing thought-provoking essays in their area of expertise, and facilitates conversations between classic social movement agenda and lines of research. 'The Oxford handbook of social movements' discusses core theoretical perspectives, recent contributions from the field, and how patterns of macro social change may affect social movements, as well as suggesting what contributions social movement studies can give to other research areas in various disc
$g1.$tIntroduction: the field of social movement studies /$rDonatella Della Porta and Mario Diani --$gPart 1.$tCore theoretical perspectives : --$g2.$tSocial movements in social theory /$rKlaus Eder --$g3.$tSocial movements in political science /$rOndæærej Câisaær --$g4.$tHistorical analysis and social movements research /$rJohn Markoff --$g5.$tContentious politics /$rSidney Tarrow --$g6.$tNew theoretical directions from the study of gender and sexuality movements: collective identity, multi-institutional politics, and emotions /$rStephen Wulff, Mary Bernstein, and Verta Taylor --$gPart 2.$tSocial movements and structural processes : --$g7.$tHistorical dynamics of capitalism and labor movements /$rBeverly J. Silver and ðSahan Savaðs Karataðsli --$g8.$tDemography and social movements /$rJack A. Goldstone --$g9.$tMigration and social movements /$rNina Eggert and Marco Giugni --$g10.$tReligious revivalism and social movements /$rLasse Lindekilde and Lene Kèuhle --$g11.$tEthnicity, nationalism, and social movements /$rDiego Muro --$g12.$tUrban dynamics and social movements /$rMassimiliano Andretta, Gianni Piazza, and Anna Subirats --$gPart 3.$tMicro-dynamics of contention : --$g13.$tMotivations to action /$rBert Klandermans --$g14.$tNetworks as constraints and opportunities /$rDavid B. Tindall --$g15.$tRational action /$rPamela E. Oliver --$g16.$tMicromobilization and emotions /$rHelena Flam --$g17.$tDemobilization and disengagement in a life course perspective /$rOlivier Fillieule --$gPart 4.$tHow movements organize : --$g18.$tSocial movements and organizational analysis /$rFrank Den Hond, Frank G.A. De Bakker, and Nikolai Smith --$g19.$tNetwork approaches and social movements /$rMario Diani and Ann Mische --$g20.$tSocial movement coalitions /$rHolly J. McCammon and Minyoung Moon --$g21.$tMovements as communities /$rHatem M. Hassan and Suzanne Staggenborg --$g22.$tNew technologies and social movements /$rJennifer Earl, Jayson Hunt, R. Kelly Garrett, and Aysenur Dal --$g23.$tCommunication in movements /$rW. Lance Bennett and Alexandra Segerberg --$g24.$tGeography and social movements /$rPaul Routledge --$gPart 5.$tRepertoires of collective action : --$g25.$tStrategy /$rJames M. Jasper, Kevin Moran, and Marisa Tramontano --$g26.$tRepertoires of contention /$rEitan Y. Alimi --$g27.$tRiots /$rDavid Waddington --$g28.$tPolitical violence /$rLorenzo Bosi and Stefan Malthaner --$g29.$tSocial mobilization and violence in civil war and social legacies /$rElisabeth Jean Wood --$g30.$tCivil resistance /$rDaniel P. Ritter --$g31.$tConsumer strategies in social movements /$rMichele Micheletti and Dietlind Stolle --$g32.$tVoluntary actions and social movements /$rHelmut K. Anheier and Nikolas Scherer --$gPart 6.$tCultures of contention : --$g33.$tCultural conflicts and social movements /$rAnne E. Tan and David A. Snow --$g34.$tNarrative and social movements /$rFrancesca Polletta and Beth Gharrity Gardner --$g35.$tThe art of social movement /$rRon Eyerman --$g36.$tVisuals in social movements /$rNicole Doerr, Alice Mattoni, and Simon Teune --$g37.$tPractice movements: the politics of non-sovereign power /$rJulia Eckert --$g38.$tImmanent accounts: ethnography, engagement, and social movement practices /$rJeffrey S. Juris and Alex Khansnabish --$gPart 7.$tPolitical and non-political opportunities and constraints : --$g39.$tContentious collective action and the evolving nation-state /$rMark R. Beissinger --$g40.$tSocial movements and the multilateral arena /$rJackie Smith --$g41.$t"The game's afoot": social movements in authoritarian states /$rHank Johnston --$g42.$tRepression: the governance of domestic dissent /$rAbby Peterson and Mattias Wahlstrèom --$g43.$tManaging protest: the politcal action repertoires of corporations /$rPhilip Balsiger --$g44.$tParty systems, electoral systems, and social movements /$rHanspeter Kriesi --$g45.$tPopulism, social movements, and popular subjectivity /$rKenneth M. Roberts --$g46.$tMarkets, business, and social movements /$rSarah A. Soule and Brayden G. King --$gPart 8.$tMovements' contributions to social and political change : --$g47.$tWelfare changes and social movements /$rColin Barker and Michael Lavalette --$g48.$tThe impacts of environmental movements /$rChristopher Rootes and Eugene Nulman --$g49.$tIs it social movements that construct human rights? /$rKate Nash --$g50.$tThe conditions for civil society participation in international decision making /$rRaffaele Marchetti --$g51.$tDemocracy in social movements /$rDonatella Della Porta --$g52.$tDemocratic innovations /$rJulien Talpin --$g53.$tRevolutions and regime change /$rJeff Goodwin and Rene Rojas.
Includes bibliographical references and indexes.
Keywords: Social movements -- History; Social change. -- History; Collective behavior. -- History